Pengaruh tingkat kewaspadaan terhadap konservatisme akuntansi - Koeswanto, Michelle Angeline; Feliana, Yie Ke; Eriandani, Rizky (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2023)
Applying conservatism in financial reporting is essential for enterprises dealing with uncertainty in a dynamic business environment. The study aims to determine the impact of uncertainty on the business environment based on the level of caution against accounting conservatism. There are two levels of alertness: alert and inert. The study used 849 samples of non-financial sector enterprises listed in the Indonesian Stock Exchange for 2019–2021. They were processing data using moderated regression. Research shows that companies with a high level of uncertainty in their business environment are less conservative. Instead, inert ones with low uncertainty about the environment are more conservative. Companies with a readiness to cope with changes in circumstances tend to be more aggressive in reporting and are likely to prefer to disclose risk factors for uncertainties rather than reporting conservatively. The research implications show that the uncertainty of the business environment based on the level of vigilance influences conservatism.